2018
DOI: 10.1007/978-1-4939-8904-1_11
|View full text |Cite
|
Sign up to set email alerts
|

An Adult Zebrafish Model of Fibrodysplasia Ossificans Progressiva

Abstract: Fibrodysplasia ossificans progressiva (FOP) is a rare human skeletal disease caused by constitutively activating mutations in the gene ACVR1, which encodes a type I BMP/TGFβ family member receptor. FOP is characterized by progressive heterotopic ossification (HO) of fibrous tissues, including skeletal muscle, tendons, and ligaments, as well as malformation of the big toes, vertebral fusions, and osteochondromas. Surgical interventions in patients often result in enhanced HO, which can exacerbate rather than im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…These transgenic lines will henceforth be known as Tg ( Dr ‐ acvr1l ‐ WTa ), Tg ( Hs ‐ R206Ha ), and Tg ( Dr ‐ R203Ha ), respectively. We previously showed that HS was an effective strategy to express the constitutively active Dr ‐ acvr1l Q204D variant in embryonic and adult zebrafish 49,57,58 . Consistent with the fact that Hs‐ACVR1 R206H signals through pSMAD1/5/8, 59 it was previously shown that injection of Hs ‐ ACVR1 R206H mRNA into single‐cell stage zebrafish resulted in increased pSmad1/5 expression and ventralization phenotypes 30 .…”
Section: Resultsmentioning
confidence: 57%
“…These transgenic lines will henceforth be known as Tg ( Dr ‐ acvr1l ‐ WTa ), Tg ( Hs ‐ R206Ha ), and Tg ( Dr ‐ R203Ha ), respectively. We previously showed that HS was an effective strategy to express the constitutively active Dr ‐ acvr1l Q204D variant in embryonic and adult zebrafish 49,57,58 . Consistent with the fact that Hs‐ACVR1 R206H signals through pSMAD1/5/8, 59 it was previously shown that injection of Hs ‐ ACVR1 R206H mRNA into single‐cell stage zebrafish resulted in increased pSmad1/5 expression and ventralization phenotypes 30 .…”
Section: Resultsmentioning
confidence: 57%
“…We confirmed these results by injection of ACVR1 R206H mRNA into single‐cell stage wild‐type (WT) zebrafish embryos, which resulted in ventralization phenotypes at 24 hpf, indicative of upregulated BMP signaling. ( 21 , 30 , 31 , 33 , 54 ) Similarly, overexpression of ACVR1 R206H in our heat‐shock inducible Tg(ACVR1‐R206Ha) model, in which Tg(ACVR1‐R206Ha) zebrafish express the human ACVR1 R206H protein fused to an mCherry fluorescent reporter under the control of the hsp70l regulatory elements (Lalonde et al Functional characterization of FOP‐Associated ACVR1 variants in embryonic zebrafish, Developmental Dynamics , in revision), showed increased ventralization phenotypes at 24 hpf.…”
Section: Resultsmentioning
confidence: 99%
“…Whole‐exome sequencing (WES) of this patient was compared to that of 19 other ACVR1 R206H FOP patients with more typical clinical disease presentations, to identify potential genetic variants that might attenuate overactive BMP signaling. We used a CRISPR/Cas9‐edited human embryonic kidney (HEK) 293T cell line and heat‐shock inducible Tg(ACVR1‐R206Ha) zebrafish ( 28 , 29 , 30 , 31 , 32 , 33 ) as models carrying the ACVR1 R206H allele to investigate how the BMPR1A and ACVR2A genes might affect ACVR1 R206H signaling activity.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrodysplasia ossificans progressiva in humans is caused by a mutation that confers the constitutive activation of the ACVR1 receptor ( Shen et al, 2009 ) and shows heterotopic ossifications (HOs) and malformations of great toes. The transgenic gain of function (GOF) of zebrafish acvr1l gene also shows HO lesions, spinal lordosis, vertebral fusions, and malformed pelvic fins, while the LOF mutants in acvr1l show loss of ventral tail tissue ( Shen et al, 2009 ; LaBonty et al, 2017 ; Mucha et al, 2018 ; LaBonty and Yelick, 2019 ). This not only supports an FOP model but also is a complementary tool to perform the genetic analysis of FOP mutations in probands.…”
Section: Zebrafish Models For Human Skeletal Diseasesmentioning
confidence: 99%